Senam Yin Yoga terhadap Penurunan Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe II (Journal of Telenursing (JOTING), 2024)
This research aims to determine the effect of yin yoga on reducing blood sugar levels with type 2 diabetes mellitus in the Karawang Regency General Hospital. The method used in this research is quantitative with a quasi-experimental design, with a pre-posttest with a control design. The results of the study showed the results of the T-test (paired sample) showed that the average blood sugar level measurement before control was 334.95 mg/dl with a standard deviation of 95.697 mg/dl. The measurement value for the respondents' sugar levels after control was an average of 251.80 mg/dl. In conclusion, both blood sugar levels during pre-intervention and pre-control had similar results.Keywords: Diabetes Mellitus Type 2, Blood Sugar Levels, Yin Yoga Exercises